2 - Crise du journalisme et de l’espace public en Afrique : quelles alternatives pour un développement du futur africain - Hien Ollo Pépin, (Africa Media Review, 2005)
There is little doubt that journalists have a power of transform, translate and oriente both behaviours and individual and collective attitudes towards ‘sociation’ or ‘dissociation’. The symbolic settings that strongly regulate the relationships between groups tend to depreciate the group to which one is confronted in a situation of political competition while reinforcing the cohesion of its circle of belonging through a minimal consensus. Social networks therefore update this already atomized, heterogonous, oppositional social space and demarcate belongings. The modalities of social competition express social exclusion and communitarian assertiveness. People from the media are now merely social agents subordinated to a structural logic. However, they also use various strategies for objectives that are already finalised. Here, we are interrogating the professionalisation of the job of journalist as something that is strongly linked to the modalities of the making of ‘public opinion’. What is the current social function of this opinion? This paper thus reflects on the impact of the press on people and on what people do with the press. The development stalemate in which Africa is stuck imposes the need to clarify and rethink the role of journalism in today’s democratising Africa—in the perspective of an African future—that is immersed in an increasingly globalizing world.